1999
DOI: 10.1002/(sici)1097-0231(19990815)13:15<1622::aid-rcm687>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-chemical ionization of diethylzinc

Abstract: The self-chemical ionization of diethylzinc is examined by Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry and semiempirical molecular orbital calculations. Electron impact of diethylzinc neutral produces the radical cation, C(4)H(15)Zn(+) (m/z x 122), which reacts further with the neutral (C(2)H(5))(2)Zn to give the following product ions: Zn(+) (m/z x 64), C(2)H(5)Zn(+) (m/z x 93), C(4)H(9)Zn(+) (m/z x 121), C(4)H(11)Zn(2)(+) (m/z x 187), and C(6)H(15)Zn(2)(+) (m/z x 215). To determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In general, ion mobility and H/D exchange results support a compact, folded conformation for both singly-and doublyprotonated bradykinin in which the basic and acidic sites interact [10,16,29]. The existence of a salt-bridge, in which the carboxy terminus is deprotonated and both arginine residues are protonated, has been proposed for singly-and doubly-protonated bradykinin [27,28]. In doubly-protonated bradykinin, the amino terminus, which is the third most basic site on the peptide, is also likely protonated in the inactivated salt-bridge structure.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…In general, ion mobility and H/D exchange results support a compact, folded conformation for both singly-and doublyprotonated bradykinin in which the basic and acidic sites interact [10,16,29]. The existence of a salt-bridge, in which the carboxy terminus is deprotonated and both arginine residues are protonated, has been proposed for singly-and doubly-protonated bradykinin [27,28]. In doubly-protonated bradykinin, the amino terminus, which is the third most basic site on the peptide, is also likely protonated in the inactivated salt-bridge structure.…”
Section: Introductionmentioning
confidence: 85%
“…The ion mobility and H/D exchange of the nonapeptide bradykinin and related analogues have been extensively studied [10,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Ion mobility measurements have shown that the singly-and doubly-protonated ions of bradykinin have a similar cross-section, while the triplyprotonated ion has a cross-section that is approximately 15% larger, providing evidence for a much less compact structure [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation